2020
DOI: 10.1007/s00280-020-04144-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase I, randomized, single-dose pharmacokinetic study comparing sb8 (bevacizumab biosimilar) with reference bevacizumab in healthy volunteers

Abstract: Purpose To compare pharmacokinetics, safety, tolerability, and immunogenicity between SB8, a bevacizumab biosimilar, and the European Union (EU) and United States (US) reference products (bevacizumab-EU, bevacizumab-US). Methods In this randomized, double-blind, parallel-group, and single-dose study, healthy volunteers were randomized to receive a 3 mg/kg dose of SB8, bevacizumab-EU, or bevacizumab-US via intravenous infusion. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
3
12
0
1
Order By: Relevance
“…The mean t 1/2 of HOT-1010 and Avastin ® was 14.6 d and 14.9 days, which was consistent with the results of other bevacizumab biosimilars (13.1-19.3 days) in Chinese, Indian, Caucasian and Korean healthy male subject studies (Knight et al, 2016;Zhang et al, 2018;Wang et al, 2019;Liu et al, 2020;Shin et al, 2020;Singh et al, 2020). The median T max of HOT-1010 (3.48 h) was similar to that of bevacizumab and other bevacizumab biosimilars (2.5-4.5 h) when intravenous dose ranged from 1 to 3 mg/kg (Zhang et al, 2018;Wang et al, 2019;Liu et al, 2020;Shin et al, 2020;Singh et al, 2020). HOT-1010 was well-tolerated and no safety concerns were identified, and safety profiles were similar between HOT-1010 group and Avastin ® group.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The mean t 1/2 of HOT-1010 and Avastin ® was 14.6 d and 14.9 days, which was consistent with the results of other bevacizumab biosimilars (13.1-19.3 days) in Chinese, Indian, Caucasian and Korean healthy male subject studies (Knight et al, 2016;Zhang et al, 2018;Wang et al, 2019;Liu et al, 2020;Shin et al, 2020;Singh et al, 2020). The median T max of HOT-1010 (3.48 h) was similar to that of bevacizumab and other bevacizumab biosimilars (2.5-4.5 h) when intravenous dose ranged from 1 to 3 mg/kg (Zhang et al, 2018;Wang et al, 2019;Liu et al, 2020;Shin et al, 2020;Singh et al, 2020). HOT-1010 was well-tolerated and no safety concerns were identified, and safety profiles were similar between HOT-1010 group and Avastin ® group.…”
Section: Discussionsupporting
confidence: 84%
“…Although the exact mechanisms are not clear yet, these AEs of HOT-1010 should be paid more attention in the future study. Additionally, 82 subjects were found to be negative for ADA test, other studies also showed the relatively low immunogenicity of bevacizumab (Knight et al, 2016;Zhang et al, 2018;Wang et al, 2019;Liu et al, 2020;Shin et al, 2020;Singh et al, 2020), the comparison of immunogenicity still needs to be further investigated with larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Similarity between SB8 and EU-sourced reference bevacizumab was demonstrated as geometric LSM ratios and their 90% CIs for AUC ∞ , AUC last and C max (primary endpoints) were within the prespecified acceptance range of 0.80–1.25 in healthy volunteers [ 4 ]…”
Section: Clinical Pharmacologymentioning
confidence: 99%
“…Pharmacokinetic similarity of SB8 to EU-sourced bevacizumab was demonstrated in a randomized, double-blind, phase 1 pharmacokinetic study in healthy volunteers [ 4 ]. The 90% CI for geometric least squares means ratios for the primary endpoints of area under the concentration-time curve (AUC) from time zero to infinity, AUC from time zero to the last quantifiable concentration and the maximum observed serum concentrations (C max ) were within the prespecified bioequivalence margin of 80.00–125.00% [ 4 ]. Furthermore, in a phase 3 study in patients with NSCLC (Sect.…”
Section: Clinical Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation